Employees Job Performance and Pursuit of Corporate Social Responsibility in the Banking Industry a Case Study of Zenith Bank Plc & First Bank Plc Jalingo - Albasu, Joseph; Nyameh, Jerome; Umar, Mahmood Hamid (Asian Journal of Social Sciences and Management Studies, 2016)
The study examine the correlation between employees job performance and corporate social responsibility, through the use of qualitative and quantitative research design paradigm, to do that effective there research objectives and two hypotheses were design; (1)To identify the contribution of employees job performance to corporate social responsibility (ii)To determine ways how corporate social responsibility can be improve in organization (iii)To analyzes the organizational excellence and the corporate social responsibility under the period under review. H1: there is a positive relationship between employee’s job performance and the corporation social responsibility H0: there is no positive relationship between employee’s job performance and the corporation social responsibility, in order to find the correlation between the two variables. To test the hypotheses, correlation was conducted between the independent and dependent variable which the degree of correlation to 0.625 showing high level of correlation hence the null hypothesis is rejected and the alternative hypothesis is accepted. And the results from the content analysis of qualitative also accept the alternative hypothesis and reject the null. Cronbach alpha statistic was also conducted for test of reliability which shown 0.951 which shows that the instrument used is highly reliable. Hence the study shows that there is a positive and significant relationship between the two important variable of the study employees job performance and corporate social responsibility.